Papel do receptor Aril hidrocarbono (AhR) durante a infecção experimental por Trypanosoma cruzi - Andreia Barroso Goncalves (2014)
Aryl hydrocarbon receptor (AhR) is a known ligand-activated transcription factor which has been described as a potential target for therapeutic interventions. Upon Toxoplasma gondii and Plasmodium berghei ANKA infection, the absence AhR results in central nervous system dysfunction. However, the role of AhR in T. cruzi infection has not been well explored. T. cruzi is a protozoan parasite that causes Chagas disease, an important neglected illness. Herein, we demonstrated that AhR mRNA is modulated during T. cruzi infection in spleen and its deficiency results in higher resistance, an anticipate immune response and in lower heart inflammation. The greater control of the infection in AhR deficient mice is probably associated decreased levels of reactive oxygen species (ROS) resulting in inability of parasite to growth into the macrophages in vitro, but in vivo associates with increased inflammatory cytokines and ROS production, but not with nitric oxide. This is, to our knowledge, a demonstration about the role of AhR in the modulation of immune response and ROS production during the experimental T. cruzi infection.